The Effect Of Social Media On Individual Creativity: The Role Of Knowledge Sharing As A Mediating Variable - Fernandes Coutinho, Filomena; Kusdi; Agung (The International Journal of Accounting and Business Society, 2025)
Purpose — This study is to explore how social media influences individual creativity, particularly through the role of knowledge sharing as a mediating variable. The study aims to understand the dual nature of social media's impact on creativity—both positive, by enhancing engagement, collaboration, and knowledge sharing, and negative, by causing distractions and reduced focus. It seeks to leverage social media to improve creativity while mitigating its adverse effects, especially in educational settings Design/methodology/approach — The study employs a quantitative research approach, utilizing an online survey method to collect data. Questionnaires were distributed via Google Forms to selected respondents, specifically targeting student WhatsApp groups. The survey used a Likert scale for responses. The research is categorized as explanatory, aiming to identify and clarify causal relationships between variables. Statistical analysis was performed using SmartPLS (Partial Least Squares) software, including evaluation of the measurement model, structural model, and hypothesis testing Findings — The study indicate that both work-related and social-related social media usage have a significant positive impact on individual creativity and knowledge sharing. Knowledge sharing serves as a partial mediator in these relationships. Specifically, work-related social media usage significantly impacts knowledge sharing, with a t-statistic value of 9.941 and a significance value of 0.000. Practical implications — This study suggest that organizations can enhance employee creativity by effectively leveraging social media usage. By understanding the positive impacts of both work-related and social-related social media usage on creativity and knowledge sharing, organizations can develop strategies to foster a more collaborative and innovative work environment. This involves encouraging the use of social media platforms for professional networking, information gathering, and collaboration, which can lead to improved employee performance and creativity Originality/value — This study lie in its exploration of the dual impact of social media usage on individual creativity, particularly through the mediating role of knowledge sharing. By focusing on both work-related and social-related social media usage, the study provides insights into how these platforms can enhance creativity in educational settings. This research contributes to the understanding of how digital environments influence creativity, offering a basis for future studies in Human Resource Management and Information Systems Management. Paper type — Case Study